Micronuclei in cytokinesis-blocked lymphocytes as an index of occupational exposure to antineoplastic drugs - Garaj-Vrhovec, Vera (Radiology and oncology (Ljubljana), 1998)
In order to investigate possible DNA damiging effects of antineoplastic drugs,the micronucleus assay combined with Giemsa, DAPI and silver staining was performed. Blood samples were taken from nurses working without adequate protection in oncological department on preparing and administration of different antineoplastic drugs. Lymphocytes were cultivated in vitro at 37 degrees C. To prevent cytokinesis, at 44th cytochalasine-B at a final concentration of 3 micro g/ml was added. The results obtained indicate statistically significant increases in the total number of micronuclei in the exposed subjects compontrols. DAPI staining has revealed signal-positive and signal-negative miuclei while silver staiing has revealed Ag-NOR+ and Ag-NOR- micronuclei. Compred to controls, the number of signal-positive exposed subjects were increased, indicating a greater susceptibility of particular chromosomes to damage caused by antineopalstic agents.
Keywords: Adverse effects; Antineoplastic agents; Lymphocytes; Micronucleus tests; Occupational exposure